Juvenile gigantomastia, two cases treated by reduction mammoplasty with nipple-areola complex graft - Zuhair F. Fathallah (The Medical Journal of Basrah University, 2013)
Gigantomastia or “Gravidic macromastia” is a rare benign disorder of the breast, in which the breasts undergo a massive hypertrophy and increase in size. It may occur during marked hormonal changes as in puberty or pregnancy or after prolonged intake of certain medicine. The condition is manifested as a massive diffuse enlargement of the breast. It is usually associated with psychological effect on the patient and her family and physical disability due to excessive breast growth. This rare condition is of undetermined aetiology, which may be due to excess hormonal secretion, or hypersensitivity of the target organ to normal hormonal level. Histologically it is a glandular hyperplasia with an increase in connective tissue. This paper reports two case of gigantomastia due to hormonal changes during puberty. Ulceration and haemorrhage of the breasts complicated the picture and is the main cause of coming to surgery. Surgical procedure was subtotal mastectomy and free implantation of the nipple areola complex.